2019
DOI: 10.1073/pnas.1815046116
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA for improved detection and environmental surveillance of schistosomiasis

Abstract: Schistosomiasis is a water-based, infectious disease with high morbidity and significant economic burdens affecting >250 million people globally. Disease control has, with notable success, for decades focused on drug treatment of infected human populations, but a recent paradigm shift now entails moving from control to elimination. To achieve this ambitious goal, more sensitive diagnostic tools are needed to monitor progress toward transmission interruption in the environment, especially in low-intensity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 63 publications
5
119
0
Order By: Relevance
“…Successful detections of trematode parasites using aquatic eDNA include Ribeiroia ondatrae in North America [29], Opisthorchis viverrini in southeast Asia [30], and Fasciola hepatica and Calicophoron daubneyi in Europe [31]. Previous studies have also shown the feasibility of recovering Schistosoma mansoni DNA from both field and laboratory environments [32,33]. They have also demonstrated that Schistosoma DNA present in laboratory water decayed below levels of detection eight days after the removal of source snails [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful detections of trematode parasites using aquatic eDNA include Ribeiroia ondatrae in North America [29], Opisthorchis viverrini in southeast Asia [30], and Fasciola hepatica and Calicophoron daubneyi in Europe [31]. Previous studies have also shown the feasibility of recovering Schistosoma mansoni DNA from both field and laboratory environments [32,33]. They have also demonstrated that Schistosoma DNA present in laboratory water decayed below levels of detection eight days after the removal of source snails [33].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown the feasibility of recovering Schistosoma mansoni DNA from both field and laboratory environments [32,33]. They have also demonstrated that Schistosoma DNA present in laboratory water decayed below levels of detection eight days after the removal of source snails [33]. Collectively, this evidence is highly supportive of the potential of eDNA methods for improved surveillance of all harmful schistosome species [34], but also indicates that improvements are needed to adapt these methods to large-scale surveillance, and to identify species other than S. mansoni.…”
Section: Introductionmentioning
confidence: 99%
“…The use of environmental DNA (eDNA) has been demonstrated to be useful in tracking S. japonicum in water through quantitative PCR (qPCR) [28,29]. It was also successfully applied to other schistosome species, such as S. mansoni in field samples for better surveillance [30,31]. In this study, O. hupensis quadrasi eDNA was detected from soil samples.…”
Section: Introductionmentioning
confidence: 97%
“…Further, the increasing capacity of sequencing technologies has expanded the value of non-destructive sample collection techniques and allows researchers to inexpensively archive samples in ethanol (Bi et al 2013, Yeates et al 2016. Newly developed eDNA techniques can make detection of free-living stages possible (Sengupta et al 2019). Complementarily, whole organism sampling designs that preserve parasite type specimens for taxonomic ground-truthing could provide reference libraries of reliable DNA barcodes.…”
Section: Collecting Parasite Data: the Way Forwardmentioning
confidence: 99%